Characterization of Plastidial and Nuclear SSR Markers for Understanding Invasion Histories and Genetic Diversity of Schinus molle L. - Rafael Plá Matielo Lemos; Cristiane Barbosa D’Oliveira Matielo; Dalvan Carlos Beise; Vanessa Gonçalves da Rosa; Deise Schröder Sarzi; Luiz Fernando Würdig Roesch; Valdir Marcos Stefenon (Biology, 2018)
Invasive plant species are expected to display high dispersal capacity but low levels of genetic diversity due to the founder effect occurring at each invasion episode. Understanding the history of invasions and the levels of genetic diversity of such species is an important task for planning management and monitoring strategy for these events. Peruvian Peppertree (Schinus molle L.) is a pioneer tree species native from South America which was introduced in North America, Europe and Africa, becoming a threat to these non-native habitats. In this study, we report the discovery and characterization of 17 plastidial (ptSSR) and seven nuclear (nSSR) markers for S. molle based on low-coverage whole-genome sequencing data acquired through next-generation sequencing. The markers were tested in 56 individuals from two natural populations sampled in the Brazilian Caatinga and Pampa biomes. All loci are moderately to highly polymorphic and revealed to be suitable for genetic monitoring of new invasions, for understanding the history of old invasions, as well as for genetic studies of native populations in their natural occurrence range and of orchards established with commercial purposes.